Mechanism and Preclinical Models of Neuropathic Pain: An Update - Melkani, Indu; Kumbhar, Prashant; Parasher, Pankaj; Kumar, Shubham; Himani; Kumar, Bimlesh; Mazumder, Rupa (Trends in Immunotherapy, 2025)
Neuropathic pain is a debilitating condition that is a product of nervous system damage or dysfunction. Since the drugs prescribed by the physician provide partial pain relief to the patients. Hence, current updates for its treatment are required. It is a global concern as neuropathic pain happens in many diseased conditions like cancer, trauma, surgery and diabetics, etc. Developed as well as developing countries are both trying to find suitable medicine. Understanding the mechanisms behind it can be crucial for the effective treatment and management of neuropathic pain. Central sensitization in the spinal cord and brain amplifies pain signals, increasing pain sensitivity even without tissue damage. Peripheral sensitization, at the injury site, sensitizes peripheral nerves, lowering pain thresholds. Recognizing and studying these sensitizations are vital for understanding and managing chronic neuropathic pain and improving patients’ quality of life. The present manuscript encompasses a mechanism and model for neuropathic pain in animals with its advantages and disadvantages.